Effects of Waste Glass as a Partial Replacement of Coarse Aggregate on Concrete Performance - Alaraj, Mohammed Ahmed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
[Abstract Not Available]
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Supervisor: Assist. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Aggregates (Building materials)--Concrete; Construction Engineering--Supplementary Cementitious Materials--Waste Glass; Waste Glass (WG); Silica fume; Glass Powder; Mechanical properties; Workability; Durability; Compressive Strength; Splitting Tensile Strength; Flexural Strength; Impact Test; Alkali-Silica Reaction (ASR); Accelerated Carbonation; Water Absorption Capacity